ANALISIS PERAN UNI EROPA TERKAIT PELANGGARAN HAK KEKAYAAN INTELEKTUAL DALAM AKTIVITAS ILLEGAL DOWNLOADING STUDI KASUS: THE PIRATE BAY - Fathony, Muhammad Ardine; Putranti, Ika Riswanti (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
The Pirate Bay is one of the gigantic peer-to-peer (P2P) sites with the origin server was Sweden which until now has become a portal for illegal downloading activities in the digital world. Praised and favored combined with defense mechanisms makes the site that released in 2003 is still working. Even though it highly criticized by various backgrounds such as the state, industry, even the international organizations the site remains exist as a liability threat as infringement of right-holders in the digital world. Categorized as cybercrime, the European Union has intention to overcome intellectual property rights violations that are actualized through the Pirate Bay’s P2P platform. Regarding to the case study, through the Supranationalism principle and the concept of Republicanism of Liberalism, the European Union plays a role in accordance with the authority, as initiator of legal products which has mutual agreements among its members, including legal consequences relating to the issue of indirect violations of intellectual property rights. In addition, the role of the European Union is also based on the Spillover effect scheme, in which the European Union's efforts are to address intellectual property violations, moreover the other cybercrime issues. Start by overcoming The Pirate Bay as analogical step by sweep-out digital-age of piracy as a symbol of an Eropean Union resistance and supremacy against the giant pirates of the digital ocean.